From the Vice-Chancellor’s Desk: Leading with Values, Inspiring Through Action - Yatimah, Alias (UMPSA, 2025)
After five months at Universiti Malaysia Pahang Al Sultan Abdullah (UMPSA), I would like to take this opportunity to share a few reflections with the UMPSA community.